On Teachers, Misses, and other Pedagogical Vicissitudes. Women in the History of Education in Antioquia 1903 – 1930 - Cruz, Carlos Arturo Ospina (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The purpose of this article is to assess the working conditions of female teachers of the instructionist oficial education system in the department of Antioquia, at the beginning of the twentieth century. This relection is based on the information gathered from oficial documents, reports, and some opinion pieces, related to the national education system between 1903 and 1930, a context in which, although women were majorityin the educative labor, they had to face a hard struggle to gain participation in pedagogical discussions conceptually addressed by male teachers. By 1903, the 75% of the teacher profession in Antioquia was constituted by women. However,in the local scenarios where methodological, philosophical, and teaching issues related to the instructionist system were discussed, resistance to female participation appearedfrom different social sectors. This article shows how, despite the fact that women from Antioquia worked actively for the education of children in schools, this was considered irrelevant in allowing their participation in reformist debates.